2021
DOI: 10.1073/pnas.2106947118
|View full text |Cite
|
Sign up to set email alerts
|

Functional succinate dehydrogenase deficiency is a common adverse feature of clear cell renal cancer

Abstract: Reduced succinate dehydrogenase (SDH) activity resulting in adverse succinate accumulation was previously considered relevant only in 0.05 to 0.5% of kidney cancers associated with germline SDH mutations. Here, we sought to examine a broader role for SDH loss in kidney cancer pathogenesis/progression. We report that underexpression of SDH subunits resulting in accumulation of oncogenic succinate is a common feature in clear cell renal cell carcinoma (ccRCC) (∼80% of all kidney cancers), with a marked adverse i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…SDH inhibition could restore ferroptotic cell death. A recent study showed that SDH dysfunction leads to the accumulation of succinate, resulting in a gain of 5-methylcytosine, and eventually enhancing the invasiveness of ccRCC by inhibiting ten-eleven translocation-2 activity [ 60 ]. As SDH is the only complex that takes part in both the TCA cycle and OXPHOS, succinate accumulation leads to the succination of Keap1, NRF2 stabilization, and the transcriptional activation of stress-response genes, thus promoting the antioxidant phenotype [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…SDH inhibition could restore ferroptotic cell death. A recent study showed that SDH dysfunction leads to the accumulation of succinate, resulting in a gain of 5-methylcytosine, and eventually enhancing the invasiveness of ccRCC by inhibiting ten-eleven translocation-2 activity [ 60 ]. As SDH is the only complex that takes part in both the TCA cycle and OXPHOS, succinate accumulation leads to the succination of Keap1, NRF2 stabilization, and the transcriptional activation of stress-response genes, thus promoting the antioxidant phenotype [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, molecular patterns involving metabolic pathways correlated with worse survival in ccRCC, including downregulation of AMP-activated kinase (AMPK) complex and the Krebs cycle genes, upregulation of genes involved in the pentose phosphate pathway and fatty acid synthesis (15). Functional deficiency of succinate dehydrogenase (SDH), resulting in succinate accumulation, is a common feature in up to 80% of ccRCCs (16). Survival analyses of the TCGA-KIRC dataset confirmed poor survival rates in case of lower expression of the SDH subunits SDHB, SDHC and SDHD (16).…”
Section: Rcc Metabolismmentioning
confidence: 97%
“…Functional deficiency of succinate dehydrogenase (SDH), resulting in succinate accumulation, is a common feature in up to 80% of ccRCCs (16). Survival analyses of the TCGA-KIRC dataset confirmed poor survival rates in case of lower expression of the SDH subunits SDHB, SDHC and SDHD (16). Notably, RCC tumors show a remarkable metabolic heterogeneity (17,18), however, still little is known how specific cellular components of the TME contribute to therapy response or resistance mechanisms.…”
Section: Rcc Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly silencing of the NNMT gene itself does not influence the level of metabolites but fumarate which concentration was substantially reduced. It could result from increased methylation of SDH gene promoter and reduced SDH transcription rate [Aggarwal et al, 2021, and for rev. Hawkins et al, 2018].…”
Section: Silencing Of Nnmt-encoding Gene Prevents Lps-evoked Effectsmentioning
confidence: 99%